Decline of a North American rocky intertidal foundation species linked to extreme dry, downslope Santa Ana winds - Whitaker, Stephen G.; Raimondi, Peter T.; Smith, Jayson R.; Lenihan, Hunter S.; Gaines, Steven D.; Miller, Robert J. (Frontiers in Ecology and Evolution, 2024)
Foundation species are essential to ecosystem function, but their role as habitat providers is predicated on their spatial dominance. Worldwide, kelps, seagrasses, corals, and other marine foundation species have declined. This is true also for rockweeds, the canopy-forming analog of subtidal kelp forests in temperate rocky intertidal ecosystems. On the west coast of North America, dense beds of the rockweed Silvetia compressa occur across large biogeographic regions, benefitting numerous species by ameliorating physical stress caused by sun exposure, desiccation, heat, and wave disturbance. Like many rockweed species, Silvetia is long-lived, slow-growing, and shortdispersing -characteristics that reduce its resilience to disturbance. We analyzed canopy cover data from 30 sites spanning 18 years and found that the rockweed had declined markedly, particularly at sites south of the major biogeographic break, Point Conception (PC), including the California Channel Islands and southern California mainland. Above PC, Silvetia trends were highly variable, but most populations remained stable or increased in cover during the survey period. This latitudinal pattern suggests that rockweed may be more stressed in its southern range. Using a generalized additive mixed-effects model with explicit spatial effects, we tested the hypothesis that Silvetia population trends are tightly linked to atmospheric climate conditions, particularly Santa Ana wind events (SAWs): strong, hot, and dry downslope winds that originate inland and move offshore. We found a highly significant negative effect of dewpoint depression, a measure of moisture content in the atmosphere, on Silvetia cover across all three regions in this study. Our results suggest that any increases in the frequency or intensity of SAWs are likely to lead to large declines and possible extirpation of Silvetia, as well as the important ecological services the species provides.